Primary peritoneal carcinoma: experience with cytoreductive surgery and combination chemotherapy. Issue 1 (1st January 2006) - Nam, J. H.; Kim, Y. M.; Jung, M. H.; Kim, K. R.; Yoo, H. J.; Kim, D. Y.; Kim, J. H.; Kim, Y. T.; Mok, J. E.
Abstract : The objective of this study was to review the clinical outcome and prognosis of patients with primary peritoneal carcinoma (PPC) treated with cytoreductive surgery and combination chemotherapy. We retrospectively reviewed the charts of 27 patients with histologically confirmed PPC, treated between March 1990 and February 2004 at Asan Medical Center, South Korea. The review included demographic data, pathologic findings, treatments, and outcomes. The mean age of the 27 patients was 57.5 ± 7.2 years, and the rate of optimal cytoreduction was 70.4%. Seven patients had stage IIIB, 17 had stage IIIC, and 3 had stage IV; all patients received adjuvant chemotherapy. There were 4 patients with progressive disease, 5 partial responders, and 15 complete responders; the remaining 3 patients were nonevaluable. At the time of the review, 10 patients were alive without evidence of disease, 3 were alive with disease, and 14 had died from disease. The median overall survival time was 41 months, and the overall 5-year survival rate was 18.1%. Patients who had optimal cytoreduction had a longer median survival (42 months) than those who had suboptimal cytoreduction (10 months; P < 0.05). Combination chemotherapy after optimal cytoreductive surgery may be effective in the treatment of patients with PPC.